Comparison of robot versus fluoroscopy-assisted pedicle screw instrumentation in adolescent idiopathic scoliosis surgery: A retrospective study - Hou, Canglong; Yang, Huan; Chen, Yu; Yang, Yilin; Zhang, Beichen; Chen, Kai; Li, Ming; Yang, Mingyuan; Chen, Kai (Frontiers in Surgery, 2023)
The aim of this study is to explore whether robot-assisted technique has advantages over conventional fluoroscopy-assisted technique in clinical and radiological outcomes and whether it could decrease the incidence of mis-implantations of pedicle screws in AIS correction surgery. A total of 101 AIS patients were recruited (RA group: 45 patients underwent robot-assisted screw insertion; FA group: 56 patients underwent fluoroscopy-assisted screw insertion). When compared the radiological data between two groups, major and secondary curves were both corrected proficiently with no difference in the Cobb angle comparison at last follow-up, suggesting that both robot-assisted technique and fluoroscopy-assisted technique could lead to efficient radiographic correction and similar clinical outcomes (all, P>0.05). In RA group, operation time, blood loss and transfusion volume were significantly greater than those in FA group, while the accuracy of screw implantations in AIS patients with thoracic scoliotic curve in RA group was higher than that in FA group. In conclusion, both robot-assisted and fluoroscopy-assisted technique could approach proficient radiographic correction and similar clinical outcomes in AIS surgery. Compared with conventional fluoroscopy technique, robot-assisted technique might improve the accuracy of screw implantations in AIS patients with thoracic scoliotic curve, while the increased operation time, blood loss and transfusion volume might be the disadvantages due to preliminary stage of learning curve.